Spatial Variation of Reservoir Properties in Onshore Dove Field of the Niger Delta Region, Nigeria - P.T. John; G. Emujakporue; D.C. Okujagu (Journal of Applied Sciences and Environmental Management)
Spatial variation of reservoir properties in Dove Field, onshore Niger Delta was evaluated using standard seismic and well log information for six wells. Pattern maps, Sequential Gaussian Simulation (SGS), and geostatistics Variogram, were used to determine the reservoir spatial variation property. The result revealed a Porosity range of 24% to 33% signifying possible hydrocarbon pore volume with an all-round interconnected pore space. Water saturation range 26% to 37%, with regions above 35% are seen as Aquifer. Shale volume range is 10% to 40%, indicating a good and efficient zone of shaly sand dispersal. Permeability range 600mD to 1600mD, with high permeability ranges of 800mD to 1200mD at the north-east section of the wells. High reservoir deliverability is anticipated within the producing zone of the Dove field considering its hydrocarbon pore volume as seen from the comparison of the Net-to-gross range of 55% to 85%, with the shale portion. The average values of porosity, permeability, shale volume, water saturation and netto-gross in the Dove field are 28%, 800mD, 13%, 32% and 85%, which are typical of the Niger Delta and can serve as a basis for decision making in the Dove field.